Patient Satisfaction Analysis Based on Hospital Service Quality - Ayu Miarsih; Saputra Adiwijaya; Soesilo Wibowo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The purpose of this study was to analyze the level of outpatient satisfaction at Sultan Imanuddin General Hospital, Pangkalan Bun. This study used a quantitative approach, with a cross-sectional design and using a Likert scale. Data collection techniques used were documentation, observation, and interview techniques. With a sample size of 132 people. Based on the results of the analysis conducted by the researcher, it can be seen that there is a significant relationship between reliability and patient satisfaction, there is a significant relationship between assurance and patient satisfaction, there is a significant relationship between empathy and patient satisfaction, there is a significant relationship between responsiveness and patient satisfaction, but there is no significant relationship between physical evidence and patient satisfaction at Sultan Imanuddin General Hospital, Pangkalan Bun. Where the most influential aspect of patient satisfaction is empathy, which includes an attitude of attention and concern for patient needs.